Institutional Arrangements in Post-Conflict Contexts: the Land Commission and the Governance Commission in Post-War Liberia - Alžběta Šváblová (Modern Africa, 2014)
The paper analyzes the role of the Land Commission and  the Governance Commision in the post-conflict institutional and  political landscape in Liberia. Problems related to land still have a  high conflict potential in the country, and are interconnected with  different fields and aspects of peacebuilding and development. Bad  governance is frequently mentioned as one of the causes of the civil  war, and governance reform is a large-scale, ambitious project with  a crucial impact on the way the country will be administered in the future. Both issues are highly sensitive and belong to the very core of state sovereignty. The paper focuses on the similarities and differences in the functioning of these two bodies in the context of power relations that shape the current political landscape in Liberia, especially with regard to the involvement of internal and external actors.